Public sector accounting - Jones, Rowan; Pendlebury, M. W. (Financial Times Prentice Hall, 2010)
This book provides a comprehensive examination of the special issues concerning accounting in the public sector of the economy, discussing why public sector accounting is different from accounting for business organisations